Delhi's education revolution : teachers, agency and inclusion. - Anand, Kusha (UCL Press, 2022)
In 2015, the Aam Aadmi Party (AAP) was elected to govern Delhi promising to improve public services, including education through government schools that would be the equal of private-school provision. Media reports, along with the party's re-election in 2020, suggest strong public confidence that AAP are delivering on that promise. But is this success reflected by experience in schools?Delhi's Education Revolution offers a critical evaluation of the AAP's education reforms by exploring policy and practice through the eyes of one key group: the government-school teachers tasked with making the AAP's pledge a reality. Drawing on 110 research interviews conducted via Zoom during the Covid pandemic in the summer of 2020, teachers explain how the reforms have changed their profession and practice, and whether education really has improved for children of all backgrounds. Analysis of views about critical issues such as inclusion and the pressure of achievement targets in classrooms that often contain more than 50 students, informs their observations about the reform programme itself. The study paints a more qualified picture of success than suggested elsewhere and makes a valuable contribution to the understanding of education reforms in India, and most especially, in Delhi.